Strong Antimicrobial and Healing Effects of Beta-Acids from Hops in Methicillin-Resistant Staphylococcus aureus-Infected External Wounds In Vivo - Sleha, Radek; Radochova, Vera; Malis, Jiri; Mikyska, Alexander; Houska, Milan; Krofta, Karel; Bogdanova, Katerina; Janovska, Sylva; Pejchal, Jaroslav; Kolar, Milan; Cermak, Pavel; Bostik, Pavel (Antibiotics (Basel, Switzerland), 2021)
Staphylococcus (S.) aureus is an important causative agent of wound infections with increasing incidence in the past decades. Specifically, the emergence of methicillin-resistant S. aureus (MRSA) causes serious problems, especially in nosocomial infections. Therefore, there is an urgent need to develop of alternative or supportive antimicrobial therapeutic modalities to meet these challenges. Purified compounds from hops have previously shown promising antimicrobial effects against MRSA isolates in vitro. In this study, purified beta-acids from hops were tested for their potential antimicrobial and healing properties using a porcine model of wounds infected by MRSA. The results show highly significant antimicrobial effects of the active substance in both the powder and Ambiderman-based application forms compared to both no-treatment control and treatment with Framycoin. Moreover, the macroscopic evaluation of the wounds during the treatment using the standardized Wound Healing Continuum indicated positive effects of the beta-acids on the overall wound healing. This is further supported by the microscopic data, which showed a clear improvement of the inflammatory parameters in the wounds treated by beta-acids. Thus, using the porcine model, we demonstrate significant therapeutic effects of hops compounds in the management of wounds infected by MRSA. Beta-acids from hops, therefore, represent a suitable candidate for the treatment of non-responsive nosocomial tissue infections by MRSA.
Keywords: methicillin-resistant; Staphylococcus aureus; infection; porcine model; hops